Rancang Aplikasi Sistem Wedding Organizer Berbasis Web pada Venna Production - Billy Faizi; Shafa Mahir; Wildan Tino Fauzan; Perani Rosyani (CV. Multi Kreasi Media, 2022)
A large number of orders are made and received in the administration of the Wedding Organizer, so that data search will be inefficient in terms of time and effort by using a manual system. So that at this time a more structured Wedding Organizer management administration system is needed in order to speed up the search for existing data and report generation, so the authors feel the need to design a Web-Based Wedding Organizer System Website that is considered necessary and helps the Wedding Organizer manager. This website is designed using HTML, JavaScript, and CSS. Because it is web-based, this Wedding Organizer application displays several testimonials and package options that customers can choose directly. This website can be accessed anywhere and customers can directly press the booking button that leads to the Google Form or if there are still questions, they can press the contact me button to directly contact Venna Production's WhatsApp number. The results obtained from the implementation of this Web-Based Wedding Organizer System application are that it makes it easier for the Wedding Organizer ordering process which was previously manual to become digital, as well as greatly assisting customers in making orders.